Wideband 5.8 GHz Radio Frequency Amplifier with 3 dB Π- Network Attenuator Isolation - Othman , A. R; Hamidon , A. H; Husain , M.N; Johal , M.S; Ibrahim , A.B (UTEM, 2011)
This paper presents a design of radio frequency amplifier (RFA), which operates at 5.8 GHz frequency for WiMAX application. The RFA designed used T-matching network consisting of lump reactive elements, 3 dB attenuator and microstrip line at the input and output impedance. The RFA developed in this project contribute a gain of 15.6 dB with overall noise figure of 2.4 dB. The overall measured bandwidth measures is 1.240 GHz with S parameters S11, S12 and S22 measured are -12.4 dB, -25.5 dB and -12.3 dB respectively. The RFA used FET transistor EPA018A from Excelics Semiconductor Inc.